2014
DOI: 10.1007/jhep03(2014)009
|View full text |Cite
|
Sign up to set email alerts
|

Chiral dynamics in a magnetic field from the functional renormalization group

Abstract: Abstract:We investigate the quark-meson model in a magnetic field using the functional renormalization group equation beyond the local-potential approximation. Our truncation of the effective action involves anisotropic wave function renormalization for mesons, which allows us to investigate how the magnetic field distorts the propagation of neutral mesons. Solving the flow equation numerically, we find that the transverse velocity of mesons decreases with the magnetic field at all temperatures, which is most … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
62
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 108 publications
(211 reference statements)
6
62
1
Order By: Relevance
“…But these claims were later challenged by the results of Ref. [55] that used a functional renormalization group approach to demonstrate that the constituent quark mass increases with the magnetic field at all temperatures and concluded that despite a strong anisotropy in the meson propagation, their fluctuations do not lead to the inverse magnetic catalysis claimed in [54]. In view of this, we expect that a similar behavior to the one found in [55] should occur in the case of the inhomogeneous chiral condensate.…”
Section: Discussionmentioning
confidence: 83%
“…But these claims were later challenged by the results of Ref. [55] that used a functional renormalization group approach to demonstrate that the constituent quark mass increases with the magnetic field at all temperatures and concluded that despite a strong anisotropy in the meson propagation, their fluctuations do not lead to the inverse magnetic catalysis claimed in [54]. In view of this, we expect that a similar behavior to the one found in [55] should occur in the case of the inhomogeneous chiral condensate.…”
Section: Discussionmentioning
confidence: 83%
“…The qualitative behavior of the transition temperature for physical quark masses is in disagreement with model calculations using either the (Polyakov-loop extended) Nambu-Jona-Lasinio ((P)NJL) model or the (Polyakov-loop extended) quarkmeson model ((P)QM); in these models, the critical temperature is an increasing function of the magnetic field, see e.g. [10][11][12][13][14][15][16][17][18][19][20]. Possible resolutions to the disagreement have been suggested [21][22][23][24][25][26][27][28] and we will discuss these at the end of the paper.…”
Section: Introductionmentioning
confidence: 77%
“…In this case one sets the wave-function renormalization factors equal to one. 2 Going beyond the local-potential JHEP04(2014)187 approximation, one would have to solve a set of coupled equations for the wave-function renormalization factors as done in the recent paper by Kamikado and Kanazawa [19]. 3 Moreover, since the SU(2) A symmetry is broken by the magnetic field, as explained above, the effective potential is therefore a function of these two invariants.…”
Section: Jhep04(2014)187mentioning
confidence: 99%
“…When the magnetic field disappears, there is no more quark dimension reduction, the integration d 3 p/(4E 2 f − ω 2 ) ∼ dp becomes finite at ω = 2m q , and there is no more such a mass jump, see the upper panel of Fig.2. It is also necessary to point out that, in hadron models like chiral perturbation theory and linear sigma model where hadrons are taken as elementary particles, the mass of the Goldstone mode changes with temperature continuously [29,33].…”
mentioning
confidence: 99%